Structural brain changes related to bilingualism: does immersion make a difference? - Stein, Maria; Winkler, Carmen; Kaiser, Anelis; Dierks, Thomas (Frontiers in Psychology, 2014)
Within the field of neuroscientific research on second language learning, considerable attention has been devoted to functional and recently also structural changes related to second language acquisition. The present literature review summarizes studies that investigated structural changes related to bilingualism. Furthermore, as recent evidence has suggested that native-like exposure to a second language (i.e. a naturalistic learning setting or immersion) considerably impacts second language learning, all findings are reflected with respect to the learning environment. Aggregating the existing evidence, we conclude that structural changes in left inferior frontal and inferior parietal regions have been observed in studies on cortical grey matter changes, while the anterior parts of the corpus callosum have been repeatedly found to reflect bilingualism in studies on white matter connectivity. Regarding the learning environment, no cortical changes can be attributed specifically to naturalistic or classroom learning. With regard to white matter changes, one might tentatively propose that changes in IFOF and SLF are possibly more prominently observed in studies investigating bilinguals with a naturalistic learning experience. However, future studies are needed to replicate and strengthen the existing evidence and to directly test the impact of naturalistic exposure on structural brain plasticity.